Global Elastodynamic Performance Criterion of Manipulators with Flexible Joints - Lara-Molina, Fabian A.; Dumur, Didier (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2022)
This paper proposes a novel design criterion for manipulators with flexible joints based on elastodynamic performance. Consequently, the elastodynamic performance is assessed; the eigenvalue problem is solved to determine the first natural frequency based on the manipulator's inertia and stiffness matrices. Then, the elastodynamic criterion is evaluated within a region of the Cartesian workspace in order to obtain a global measure. The global elastodynamic performance of a planar serial manipulator and a planar parallel manipulator with flexible joints were obtained. The numerical results show a high dependency of the elastodynamic performance on the configuration and geometric parameters of the manipulator.